Development and characterization of recombinant tick-borne encephalitis virus expressing mCherry reporter protein: A new tool for high-throughput screening of antiviral compounds, and neutralizing antibody assays - Haviernik, Jan; Eyer, Ludek; Yoshii, Kentaro; Kobayashi, Shintaro; Cerny, Jiri; Nougairède, Antoine; Driouich, Jean-Sélim; Volf, Jiri; Palus, Martin; de Lamballerie, Xavier; Gould, Ernest A.; Ruzek, Daniel (Antiviral research, 2021)
The flavivirus, tick-borne encephalitis virus (TBEV) is transmitted by Ixodes spp. ticks and may cause severe and potentially lethal neurological tick-borne encephalitis (TBE) in humans. Studying TBEV requires the use of secondary methodologies to detect the virus in infected cells. To overcome this problem, we rationally designed and constructed a recombinant reporter TBEV that stably expressed the mCherry reporter protein. The resulting TBEV reporter virus (named mCherry-TBEV) and wild-type parental TBEV exhibited similar growth kinetics in cultured cells; however, the mCherry-TBEV virus produced smaller plaques. The magnitude of mCherry expression correlated well with progeny virus production but remained stable over <4 passages in cell culture. Using well-characterized antiviral compounds known to inhibit TBEV, 2′-C-methyladenosine and 2′-deoxy-2′-β-hydroxy-4′-azidocytidine (RO-9187), we demonstrated that mCherry-TBEV is suitable for high-throughput screening of antiviral drugs. Serum samples from a TBEV-vaccinated human and a TBEV-infected dog were used to evaluate the mCherry-based neutralization test. Collectively, recombinant mCherry-TBEV reporter virus described here provides a powerful tool to facilitate the identification of potential antiviral agents, and to measure levels of neutralizing antibodies in human and animal sera. •The mCherry-TBEV reporter virus was established.•mCherry-TBEV and wild-type TBEV exhibit similar growth kinetics in cultured cells.•mCherry-TBEV is suitable for high-throughput screening of antiviral drugs.•mCherry-TBEV can be used to measure levels of neutralizing antibodies in human and animal sera.